Implementasi Model Savi Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPS Tentang Kenampakan Alam dan Keragaman Sosial Budaya Kelas IV SD Negeri 50 Kota Ternate - Sufri Saleh (Peneliti.net, 2022)
The purpose of this research is to describe the application of the SAVI model through social studies learning about natural appearances and socio-cultural diversity in improving the learning outcomes of fourth grade students at SD Negeri 50 Ternate City. The research hypothesis is that if social studies learning is through the SAVI model, then the student learning outcomes in class IV SD Negeri 50 Ternate City reach a minimum of 70%. The conclusions of this study are: Research on the application of the SAVI model in improving student learning outcomes in social studies subjects about natural appearance and socio-cultural diversity of class IV SD Negeri 50 Ternate City is successful, this can be seen from the enthusiasm, attention to the role and motivation of students increase when the teacher guides each student. In Cycle I, the student learning outcomes who completed at least 70%, while those who completed Cycle I were 8 (25%) and 24 students (75%). After being continued with Cycle II, there was an increase in student learning outcomes. 28 students (87%) completed and 4 students did not complete (12%).